PD-L1+ Lymphocytes Are Associated with CD4+, Foxp3+CD4+, IL17+CD4+ T Cells and Subtypes of Macrophages in Resected Early-Stage Non-Small Cell Lung Cancer - Gurevičienė, Giedrė; Matulionė, Jurgita; Poškienė, Lina; Miliauskas, Skaidrius; Žemaitis, Marius (International journal of molecular sciences, 2024)
The non-canonical PD-L1 pathway revealed that programmed-death ligand 1 (PD-L1) expression in immune cells also plays a crucial role in immune response. Moreover, immune cell distribution in a tumour microenvironment (TME) is pivotal for tumour genesis. However, the results remain controversial and further research is needed. Distribution of PD-L1-positive (PD-L1+) tumour-infiltrating lymphocytes in the context of TME was assessed in 72 archival I–III stage surgically resected NSCLC tumour specimens. Predominant PD-L1+ lymphocyte distribution in the tumour stroma, compared to islets, was found (p = 0.01). Higher PD-L1+ lymphocyte infiltration was detected in smokers due to their predominance in the stroma. High PD-L1+ lymphocyte infiltration in tumour stroma was more common in tumours with higher CD4+ T cell infiltration in islets and stroma, Foxp3+CD4+ T cell infiltration in islets and lover M1 macrophage infiltration in the stroma (p = 0.034, p = 0.034, p = 0.005 and p = 0.034 respectively). Meanwhile, high PD-L1+ lymphocyte infiltration in islets was predominantly found in tumours with high levels of IL-17A+CD4+ T cells in islets and Foxp3+CD4+ T cells in islets and stroma (p = 0.032, p = 0.009 and p = 0.034, respectively). Significant correlations between PD-L1+ lymphocytes and tumour-infiltrating CD4+, Foxp3+CD4+, IL-17A+CD4+ T cells and M2 macrophages were found. An analysis of the tumour-immune phenotype revealed a significant association between PD-L1 expression and IL17+CD4+ and Foxp3+CD4+ immune phenotypes. PD-L1+ lymphocytes are associated with the distribution of CD4+, Foxp3+CD4+, IL17A+CD4+ T cells, M1 and M2 macrophages in TME of resected NSCLC.